PERANAN KRIPTOGRAFI DALAM PENINGKATAN PENGAMANAN SISTEM INFORMASI - Purwanto, Dedi (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
Current technological advances have affected almost all aspects of human life, which can make it easier to exchange data quickly, including in terms of communication. However, in exchange of data, it is still very poorly realized. One of the negative impacts is data theft. Therefore, the security aspect of information exchange and data storage is very important. Especially in the automotive retail sector, where there is a lot of important and confidential data such as customer identity data and financial reports. Because the data is so important, we need a method that can maintain the confidentiality of the data and the method in question is cryptography. The algorithm used is chriptogtaphic algorithm. This algorithm is part of an asymmetric algorithm, each encryption and decryption process has a different key. The purpose of this research is to find a way to implement the cryptographic algorithm into a real application and to produce a desktop-based data security application that is easy to understand and use by the user. This research uses data collection and development methods. The results of this study will be implemented in an application program using a Java-based desktop programming language that makes it easy for everyone who wants to secure important files. In this application the user must create a public key before the encryption process and a private key before the decryption process on the file.Keywords: Floyd Warshall Algorithm, Karo District, GIS